ASSESSMENT OF MANAGEMENT MODULES AGAINST LEAF CURL DISEASE IN CHILLI - S. BHUSHAN; H. K. CHAURASIA; RAVI SHANKER (The Bioscan, 2020)
Field experiments were carried out during the year 2017 – 18 and 2018 – 19 to assess the different management modules against the leaf curl disease in chilli. The result on efficacy of modules revealed that during both the years of trial all the modules significantly reduced the disease incidence. Module having seed treatment with Imidacloprid 70 WS (10g/Kg seed), destruction of infested plants and spraying with Imidacloprid 17.8 SL (0.3 ml/litre water) exhibited the minimum leaf curl disease incidence (19.5% during the year 2017 – 18 and 18.0% during the year 2018 - 19) in chilli. Maximum yield (138.4 and 124.2 q/ha during the year 2017 – 18, 2018 – 19, respectively) was also observed in the same module.